Niektóre wyzwania pod adresem metody teologii - Królikowski, Janusz (Poznańskie Studia Teologiczne, 2016)
This study focuses on two issues, namely: the issue of the contemplative character of theology (it deals with the nature of theology), and the question of how other academic disciplines – especially anthropological ones – may contribute to theology. The latter is an attempt to point out certain possible interdisciplinary applications of theology, and to open to the subject of its study and to the formulated proposals concerning particularly understanding of man and his life on earth. The issue of a contemplative character of theology, deeply rooted in its own history, has to struggle today with two phenomena: anthropological reductionism and the preference given to action. The question then arises: why cannot such tendencies be accepted uncritically? Contemporary theology faces a serious challenge because it has to include in its study a positive contribution made by humanities for understanding of man. However, a question may be asked: how to take advantage of the achievements of these disciplines so that the theological reflection may preserve its specific character and serve a deeper understanding of faith and its essence.